2011
DOI: 10.1104/pp.111.176206
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the PEBP Gene Family in Plants: Functional Diversification in Seed Plant Evolution    

Abstract: The phosphatidyl ethanolamine-binding protein (PEBP) gene family is present in all eukaryote kingdoms, with three subfamilies identified in angiosperms (FLOWERING LOCUS T [FT], MOTHER OF FT AND TFL1 [MFT], and TERMINAL FLOWER1 [TFL1] like). In angiosperms, PEBP genes have been shown to function both as promoters and suppressors of flowering and to control plant architecture. In this study, we focus on previously uncharacterized PEBP genes from gymnosperms. Extensive database searches suggest that gymnosperms p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
276
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(311 citation statements)
references
References 63 publications
17
276
0
Order By: Relevance
“…Natural variation in TFL1 homologs has been important for the domestication and crop improvement of several annual crops (Turnbull, 2011), and our study shows the importance of TFL1 in the perennial context. As TFL1 homologs exist in all angiosperms (Karlgren et al, 2011) and their function as floral repressors is conserved between plant families (Shannon and Meeks-Wagner, 1991;Foucher et al, 2003;Kotoda et al, 2006;Mohamed et al, 2010;Imamura et al, 2011), our findings are of general significance for understanding the regulation of flowering-and perennial-specific traits in a wide range of economically important crops.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic mentioning
confidence: 90%
“…Natural variation in TFL1 homologs has been important for the domestication and crop improvement of several annual crops (Turnbull, 2011), and our study shows the importance of TFL1 in the perennial context. As TFL1 homologs exist in all angiosperms (Karlgren et al, 2011) and their function as floral repressors is conserved between plant families (Shannon and Meeks-Wagner, 1991;Foucher et al, 2003;Kotoda et al, 2006;Mohamed et al, 2010;Imamura et al, 2011), our findings are of general significance for understanding the regulation of flowering-and perennial-specific traits in a wide range of economically important crops.…”
Section: Regulation Of Fvtfl1 Mrna Expression Controls Photoperiodic mentioning
confidence: 90%
“…It has been suggested that gymnosperms lack orthologues of FT genes, instead containing a group of FT/TFL1-like genes that probably act as flowering repressors 36,37 . We identified four putative FT/TFL1-like genes in the P.abies 1.0 genome that have not been previously described and confirmed that the genome does indeed lack FT-like genes (Supplementary Information 5.1).…”
Section: The Evolution Of Important Conifer Traitsmentioning
confidence: 99%
“…Expression of TFL1 (SbCN2) was approximately 30-fold higher in buds of phyB-1 plants at 6 DAP and approximately 80-fold higher by 8 DAP. TFL1 is a member of the phosphatidyl ethanolamine-binding protein gene family, and members of this family in Arabidopsis include FLOWERING LOCUS T (FT), MOTHER OF FT AND TFL1 (MFT), and CENTRORADIALIS homolog (ATC), genes that activate flowering (Karlgren et al, 2011). TFL1-like genes encode proteins that are expressed in meristems and bind to leaf-derived FT to prevent FT-induced flowering (Lifschitz et al, 2014).…”
Section: Maintenance Of Bud Vegetative Meristems In Phyb-1 Sorghummentioning
confidence: 99%